N-cadherin distinguishes intrahepatic cholangiocarcinoma from liver metastases of ductal adenocarcinoma of the pancreas - Gerber, Tiemo Sven; Goeppert, Benjamin; Hausen, Anne; Witzel, Hagen Roland; Bartsch, Fabian; Schindeldecker, Mario; Gröger, Lisa-Katharina; Ridder, Dirk; Cahyadi, Oscar; Esposito, Irene; Gaida, Matthias; Schirmacher, Peter; et al. (Cancers, 2022)
Carcinomas of the pancreatobiliary system confer an especially unfavorable prognosis. The differential diagnosis of intrahepatic cholangiocarcinoma (iCCA) and its subtypes versus liver metastasis of ductal adenocarcinoma of the pancreas (PDAC) is clinically important to allow the best possible therapy. We could previously show that E-cadherin and N-cadherin, transmembrane glycoproteins of adherens junctions, are characteristic features of hepatocytes and cholangiocytes. We therefore analyzed E-cadherin and N-cadherin in the embryonally related epithelia of the bile duct and pancreas, as well as in 312 iCCAs, 513 carcinomas of the extrahepatic bile ducts, 228 gallbladder carcinomas, 131 PDACs, and precursor lesions, with immunohistochemistry combined with image analysis, fluorescence microscopy, and immunoblots. In the physiological liver, N-cadherin colocalizes with E-cadherin in small intrahepatic bile ducts, whereas larger bile ducts and pancreatic ducts are positive for E-cadherin but contain decreasing amounts of N-cadherin. N-cadherin was highly expressed in most iCCAs, whereas in PDACs, N-cadherin was negative or only faintly expressed. E- and N-cadherin expression in tumors of the pancreaticobiliary tract recapitulate their expression in their normal tissue counterparts. N-cadherin is a helpful marker for the differential diagnosis between iCCA and PDAC, with a specificity of 96% and a sensitivity of 67% for small duct iCCAs and 50% for large duct iCCAs.